Pengaruh Kualitas Pelayanan Petugas Pasasi Terhadap Kepuasan Penumpang PT Gapura Angkasa di Bandar Udara - I Gusti Ngurah Rai Bali Poltak P.Y.M.B Nababan; Yulia Aji Puspitasari (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze the effect of service quality on passenger satisfaction levels at PT Gapura Angkasa at I Gusti Ngurah Rai Airport, Bali. Service quality reflects the standard of excellence provided by the company to passengers, both through planned service standards and their implementation. This research uses a quantitative method with the population consisting of all Citilink airline passengers served by PT Gapura Angkasa traffic officers each month. The sampling technique used is non-probability sampling, where participants are selected based on certain criteria. The sample size was determined using the Slovin formula, resulting in a total of 100 respondents. After the data was collected, it was processed using various analytical methods, including instrument validation, hypothesis testing, and determination coefficient assessment.The findings of this study indicate a significant positive relationship between service quality and passenger satisfaction. This is supported by the T-test results, where the calculated T-value (11.070) is greater than the critical T-value (1.984), with a significance level of 0.000, which is below 0.05. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, confirming that service quality has an impact on passenger satisfaction. Furthermore, the coefficient of determination (R²) test results reveal that service quality accounts for 83.2% of the variation in passenger satisfaction, demonstrating a substantial effect.